Na0.44MnO2/Polyimide Aqueous Na-ion Batteries for Large Energy Storage Applications - Maddukuri, Satyanarayana; Nimkar, Amey; Chae, Munseok S.; Penki, Tirupathi Rao; Luski, Shalom; Aurbach, Doron (Frontiers in Energy Research, 2021)
Aqueous salt batteries with high concentrations of salt or water in salt aqueous systems have received considerable attention with focus on improving working voltage range and energy density. Here, the effect of NaClO4 salt concentration on the electrochemical performance and stability of tunnel-type Na0.44MnO2 (NMO) cathodes and organic polyimide (PI) derivative anodes was studied. High capacity retention and 100% coulombic efficiency were shown for NMO/PI full cell in saturated NaClO4 electrolyte. A high, stable capacity of 115 mAh/g was achieved for the PI anode material, and the full cell showed a stable capacity of 41 mAh/g at 2C rate for 430 cycles (calculated for the weight of NMO cathode). Even at a fast 5C rate, a discharge capacity of 33 mAh/g was maintained for 2,400 prolonged cycles with nearly 100% efficiency. The full cell device can achieve an average voltage of 1 V with energy density of 24 Wh/kg. This study highlights concentrated sodium perchlorate as a promising electrolyte solution for stabilization of electrodes and enhancement of electrochemical performance in aqueous media.